Proyecto pedagógico de la Gran Colombia: una ruptura frente a los ideales republicanos. - García Sánchez, Bárbara Yadira (Revista Científica, 2006)
La Gran Colombia citizens have fbünded its basis at literacy education, demanding for knowing how to read and write as requirement to access on it. This condition wás especiallY difficult for most of the population, who was illiterate. The new project of nation needed to use an educational plan that offers the possibility to teach how to write and read, add and subtract to most of the people in the space of ten years. In order to achieve this goal, it was necessary to use the mutual teaching method or Lancasterian method, as an alternative for the diffusion of the first literacy and fundamental mathernatics for they that had been relegated of educational institution during colonial period. In this way, Republic propose education for everyone as a mechanism that allows to create a new social order.